Faktor-faktor yang mempengaruhi kebijakan utang pada perusahaan sektor transportation & logistics di BEI tahun 2019-2023 - Yulianto, Naufal Alief; Hartono, Ulil (Universitas Negeri Surabaya, 2025)
This study aims to analyse the influence of asset structure, managerial ownership, institutional ownership, business risk, free cash flow, and non-debt tax shield on debt policy. The population in this study comprises 37 companies in the transportation and logistics sector listed on the IDX from 2019 to 2023, with a sample of 24 companies selected through purposive sampling. Panel data regression analysis was chosen as the data analysis technique in this study by utilising STATA 17 software. The test results show that asset structure has no effect on debt policy, managerial ownership has a negative effect on debt policy, institutional ownership has a negative effect on debt policy, business risk has a negative effect on debt policy, free cash flow has no effect on debt policy, and non-debt tax shield has a positive effect on debt policy. Therefore, companies can consider managerial ownership, institutional ownership, business risk, and non-debt tax shield because these variables can affect the level of debt that the company uses as a source of funding.